Integrating sports into language teaching methodology - Antoine Sébastien Mourad; Sara Dolores González Reyes; Diana Verónica Terán Molina; Eliana Geomar León Abad (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The teaching of English as a foreign language has evolved to incorporate approaches that integrate linguistic development with intercultural and socio-emotional aspects. In this context, collaborative physical activities emerge as a strategy that promotes meaningful learning.